Teacher Training Doctoral Studies Basic Parameters and Development Vectors in Russia and in the World: The Results of the Global Study of Leading Universities - E. V. Brodovskaya; A. Yu. Dombrovskaya; A. B. Shatilov; R. V. Parma (Высшее образование в России)
The article analyzes the main trends in the development of the scientific and pedagogical personnel training system in Russia and foreign countries. The main method of collecting empirical information is quantitative content analysis of the leading universities’ site content. The case selection is based on the QS (Quacquarelli Symonds World University Rankings – 2016 and 2020) – global university ranking (top 500). The selection of Russian universities has been carried out on the basis of the QS BRICS – 2016 and 2020 university ranking. Based on the results of the selection of the leading universities, 60 universities of North and Latin America, Russia, China, Europe, and Australia have been selected. The comparison criteria of higher education institutions are codified in the content analysis matrix. We compared the entry requirements, the content and organization of the doctoral studies, and the “exit” – the learning outcomes. The results of the research are the distinctive characteristics of the Russian teacher training doctoral programs and foreign doctoral programs EdD, EdLd, PhD in Education. It is revealed that foreign universities are characterized by an orientation to a variety of labor markets, differentiation of programs and career paths; studentoriented approach; flexible choice of learning formats; focus on the preparation of the author’s original research; close attention to the idea of the dissertation research, programs, scientific publications, dissertation text, multilevel assessment (program Manager, scientific consultant, elective teachers on the topic of the dissertation, the head of the postgraduate seminar, external experts); online learning; high quality of technical and informational environment. The characteristics of the Russian doctoral studies, which impede differentiation of the paths of dissertation preparation by doctoral students depending on the specifics of the scientific research area, limit the possibility of implementing the practical results of the dissertation and reduce the potential for professional growth of doctoral students.